1999
DOI: 10.1046/j.1365-2699.1999.00274.x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental correlates of species richness for native freshwater fish in Oregon, U.S.A.

Abstract: Summary Aim To better understand how environmental factors affect fish species richness across the state of Oregon. Location Oregon, U.S.A. Methods A database showing collection locations of 4911 fish specimens in the Oregon State University museum was modified by the Oregon Natural Heritage Program to include probable occurrences, and mapped within a grid of 375 hexagons that cover the state. The individual species maps of freshwater fish in Oregon were reviewed and revised by thirty regional fish biologis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
56
0
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 72 publications
6
56
0
3
Order By: Relevance
“…Multiple linear regression was used to identify stream habitat and land cover variables that were related to invertebrate variables (exclusive of individual taxa densities). In regression analysis, all-subsets variable selection (Rathert et al, 1999;Ramsey and Schafer, 2002) was first used to select the set of stream habitat variables that best explained variation in each invertebrate assemblage variable. For each invertebrate variable, the best regression model was considered to be the one in which parameter coefficients for all stream habitat variables were significantly different (P # 0.05) from zero, and that had lowest values for Mallow's Cp statistic and Akaike's Information Criterion (Ramsey and Schafer, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple linear regression was used to identify stream habitat and land cover variables that were related to invertebrate variables (exclusive of individual taxa densities). In regression analysis, all-subsets variable selection (Rathert et al, 1999;Ramsey and Schafer, 2002) was first used to select the set of stream habitat variables that best explained variation in each invertebrate assemblage variable. For each invertebrate variable, the best regression model was considered to be the one in which parameter coefficients for all stream habitat variables were significantly different (P # 0.05) from zero, and that had lowest values for Mallow's Cp statistic and Akaike's Information Criterion (Ramsey and Schafer, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…TAN heavily contributed in dividing cluster I into two parts; the thermal range appeared to be important in the present study partly because of its vast variability (21.2 °C-56.1 °C). Since fish are poikilothermal animals, they will suffer considerably from the environment temperature change as demonstrated on some European freshwater fish (Buisson et al 2008;Pont et al 2005) and American species (Rathert et al 1999). Although each fish species has a thermal preference and can usually be characterized by a tolerance range of temperatures varying by a few degrees, they are flexible and can adapt to a certain extent by physiological adjustments or behavioral thermoregulation.…”
Section: Potential Determinants Of Lake Fish Diversity and Assemblagesmentioning
confidence: 99%
“…For instance in Northern lakes, the air temperature could cover a large range annually from warm season to cold season (Wang and Dou, 1998). Some European freshwater fishes (Buisson et al, 2010;Pont et al, 2005;Mann, 1996) and American species (Rathert et al, 1999) were also demonstrated to be great impacted by the TAR. Although each fish species has a thermal preference characterized by a tolerance range of temperatures, they are flexible and can adapt to a certain extent with physiological adjustments (Johnson and Kelsch, 1998) or behavioral thermoregulation (Heggenes et al, 1993).…”
Section: Prediction and Determinants Of Fish Species Assemblages In Cmentioning
confidence: 99%